TINJAUAN HIPOTESIS SAPIR WHORF DALAM UNGKAPAN ”SERAH TERIMA” BAHASA JEPANG - Sri Sri (FEB UNTAG Semarang, 2013)
Sapir-Whorf Hypothesis is a hypothesis which shows an interrelationship between language and the mind. In Japanese the relationship between the mind and language has created a language reality in which language is influenced by the cultures of the Japanese society. The influencing cultures are Joge Kankei (vertical relationship, upper-lower, social stratifications) and Uchi Soto (inner-outer circle of people), and one of the language elements being influenced is the ‘offering-accepting’ expression. The ‘offering-accepting’ expression for nouns is represented by the words ageru, kureru morau in the ordinary style of the language, and sashi ageru, kudasaru and itadaku in the polite style. In services teageru, te morau and te kureru are used.The use of the ‘offering-accepting’ expression is based on who is talking to whom, from which he/she comes, and what is the status of the speaker and the interlocutor. The correct use of the expression reflects an understanding of the culture of the Japanese society.